Factors associated with low utilisation of cervical cancer screening among urban women in Lilongwe, Malawi: a cross sectional study - Patricia Kamanga; Bo Zhang; William Stones (BMC, 2023)
Abstract Background In 2012, more than half a million women (528,000) were diagnosed with cervical cancer around the world. More than 80% of cervical cancer occurs in developing nations, such as Malawi, where estimates of the disease's burden show an incidence of 75.9 per 100,000 women and a mortality rate of 49.8 per 100,000 women (both age-adjusted). Despite its case fatality rate, cervical cancer can be avoided through immunization, early detection and screening. Malawi however, has low immunization and screening rates with coverage as low as 9% and 15%, respectively. Here our aim is to uncover factors that contribute to low utilization of cervical cancer screening services among women in Lilongwe, a large urban center. Methods This was a qualitative cross-sectional study. Participants were chosen at random from a big metropolitan health center. In-depth interviews and two observations were undertaken by the researchers. Interviews were taped, transcribed verbatim, and content assessed. Results A total of 24 women and 5 health workers, with an average age of 34.8 years, were questioned. 50% of women had completed secondary school, 33.3% had completed primary school, and 4% had completed no formal education. The majority of the women were housewives and entrepreneurs. 62.5% of the respondents had fewer than four children, 25% had four to six children, and 8.3% had more than six children. 91 − 6% of those surveyed were married, with 78% of Christians and 20% of Muslims. The majority of women were unaware of the importance of cervical cancer screening. Some people were concerned about marital troubles, pain during the process, "laziness," and the amount of time necessary. The majority of people would come for a test as a result of signs and symptoms. Male health personnel would be unable to screen Muslim women. All of the medical personnel had at least two years of experience. Women's low involvement in cervical cancer screening has been linked by health workers to a lack of resources and a lack of community awareness. Conclusion Cervical cancer can be prevented by early detection and treatment. Women, on the other hand, are uninformed about cervical cancer. Myths, misconceptions, cultural and religious beliefs, as well as service restrictions and community sensitization, influence the use of cervical cancer screening services. Addressing these issues has the potential to boost cervical cancer screening rates.